Urban Water Storage Capacity Inferred From Observed Evapotranspiration Recession. Issue 3 (8th February 2022) - Jongen, H. J.; Steeneveld, G. J.; Beringer, J.; Christen, A.; Chrysoulakis, N.; Fortuniak, K.; Hong, J.; Hong, J. W.; Jacobs, C. M. J.; Järvi, L.; Meier, F.; Pawlak, W.; et al.
Abstract: Water storage plays an important role in mitigating heat and flooding in urban areas. Assessment of the water storage capacity of cities remains challenging due to the inherent heterogeneity of the urban surface. Traditionally, effective storage has been estimated from runoff. Here, we present a novel approach to estimate effective water storage capacity from recession rates of observed evaporation during precipitation‐free periods. We test this approach for cities at neighborhood scale with eddy‐covariance based latent heat flux observations from 14 contrasting sites with different local climate zones, vegetation cover and characteristics, and climates. Based on analysis of 583 drydowns, we find storage capacities to vary between 1.3 and 28.4 mm, corresponding to e ‐folding timescales of 1.8–20.1 days. This makes the urban storage capacity at least five times smaller than all the observed values for natural ecosystems, reflecting an evaporation regime characterized by extreme water limitation. Plain Language Summary: Urban water storage plays an important role in mitigating urban flooding and affects urban heat via cooling through evapotranspiration (ET). Determining the amount of water that can be stored in a city remains challenging due to the variability in urban landscapes. The methodology presented estimates this water storage based on how ET declines over time during periods without precipitation. The estimated storage capacities amount to 1.3–28.4 mm, which is at least five times smaller than values that have been reported for natural ecosystems. Key Points: A new method is applied to infer urban water storage capacity from evapotranspiration recession Our analysis of evaporation observations reveals water is limiting within days in cities worldwide Water storage capacity in cities is at least five times smaller than in natural systems